PEMANFAATAN WEB CAM DENGAN METODA PRINCIPAL COMPONENTS UNTUK SISTEM PRESENSI KARYAWAN PADA KOMPUTER - Utama, Hadian. S.; Harlianto, T; Kosasih, Rudon (Universitas Tarumanagara, 2008)
This paper discuss about the applied of webcam on a presention system to verified an image of human face based on his/herself training images. This system was the biometric system because the system used some of human bodies as an object to verified. The method that used in this system was Principal Components Analysis (PCA) which can reduce the complexity of an face image into a simple set of weight. PCA used only a few of training images to verified an unknown image so it can reduce the time that waste to train the training images. The concept that used in this verification method is to compared the weight of training images with the weight of test image.